ANALYSIS OF THE IMPLEMENTATION OF NON-PROFIT FINANCIAL REPORTING BASED ON ISAK 35 - Nurazizah; Haliah (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to analyze the application of non-profit financial reporting based on ISAK 35 at Miftahul Khair Mosque, Bontonompo District, Gowa Regency. The research method used is descriptive qualitative with a case study approach. Data were collected through interviews, observations, and documentation. The results show that the financial reporting of Miftahul Khair Mosque is still very simple, covering only cash inflows, outflows, and cash balances. The implementation of ISAK 35 has not been fully applied, so the financial reports prepared do not meet the applicable accounting standards. This study recommends the need to improve transparency and accountability in mosque financial management by fully implementing ISAK 35.